Scarcity and Power in US–Mexico Transboundary Water Governance: Has the Architecture Changed since NAFTA?. Issue 6 (1st November 2016) - Mumme, Stephen P.
Abstract: This paper examines the politics of water allocation on the US–Mexico border since the North American Free Trade Agreement (NAFTA) began in 1994. While NAFTA reforms have modestly changed the water allocation regime, they have not altered the longstanding asymmetry of power relationships governing the allocation of water resources between the two countries. Two rivers are considered. On the Rio Grande, NAFTA and its associated reforms had the effect of accentuating recent allocation crises and helping to resolve them, while leaving existing power arrangements largely intact. On the Colorado River, efforts to save the Colorado River delta ecosystem after NAFTA benefitted from institutional reforms, but these efforts remain rather marginal to the longstanding structure of power governing allocation and management of Colorado River water resources, as the case of the All-American Canal dispute reveals. These cases reveal the treaty regime as one that is highly resistant to change, suggesting that caution is needed when using theoretical constructs like multilevel governance and collaborative watershed management in drawing generalizations on transboundary water management along the US–Mexican border.